Water productivity of potato under improved irrigation techniques in Uzbekistan - Djumaboev, Kakhramon; Reddy, J.M.; Carli, C.; Yuldashev, Tulkun; Anarbekov, Oyture; Eshmuratov, Davron (2019)
Potato is a very important cash crop in Uzbekistan as the government has implemented several measures to increase its production to meet food security as well as to improve its export potential. However, irrigation water demand of potato is much higher than for other crops such as sorghum and maize, which normally consume less water and generate more income. Furrow irrigation is the main irrigation method used to grow potato in Uzbekistan. Introduction of improved irrigation methods could reduce the water used for potato production and provide alternative solutions to improving potato production and income security under water scarce conditions. There are few comparative studies on conventional furrow versus improved irrigation methods for potato production. This paper explores water productivity of two varieties of potato under four irrigation treatments in Andijan and Ferghana regions of Uzbekistan. At each location, four different irrigation treatments were evaluated. These four treatments were: conventional furrow irrigation (CFI), high frequency furrow irrigation (HFI), partial root zone drying irrigation (PRD), and drip irrigation (DrI). The experimental sites in each study area were established in 2012 on farmer fields. Data on water used and agronomic performance were collected from both study sites to calculate water productivity for each treatment. Analysis of Variance (ANOVA) was used to identify differences in treatments. The results indicate that, overall, high frequency furrow irrigation and drip irrigation treatments performed better than conventional furrow irrigation and partial root drying treatments. Research findings from this paper are useful for relevant stakeholders in Uzbekistan whose population is highly dependent on irrigated agriculture. Existing water use policies in Uzbekistan do not provide water users incentives for water saving as water delivery for agriculture is highly subsidized by the government resulting in excessive water use. These findings may help reduce unsustainable water use by increasing knowledge of relevant stakeholders including decision makers in order to improve water policies in the region.